Investigation of Parental Roles in Relation to Youth Football - Szalánczi, Zoltán; Bácsné Bába, Éva (International Journal of Engineering and Management Sciences, 2023)
My research is based on the fact that, thanks to the development of sports and the capital flowing into the sector, youth sports are no longer just a useful way of spending free time for children and a mean for educating them for a healthy lifestyle, but also an opportunity to lay the foundation for an adult sports career and, with it, secure future existence. In order for the training to be effective and productive, one of the many components is the existence of parental support. Youth competitive sports pose many challenges for a family and influence their lives from several aspects. In my research, I examined how youth sports affects parents in terms of certain demographic variables, what changes it generates in their family life, and I also paid attention to what expectations the family has about sports. The basis of the study is an online questionnaire survey, which was filled out by more than 700 parents of youth football associations. My research revealed that, in accordance with the previous literature related to the topic, their children’s sports have a significant impact on the lives of the parents and they set different expectations regarding it, which are also influenced by various social and demographic factors.